Microbiological quality and pH changes of honey produced by stingless bees, Heterotrigona itama and Geniotrigona thoracica stored at ambient temperature - Lani M.N.; Zainudin A.H.; Razak S.B.A.; Mansor A.; Hassan Z. (Malaysian Society of Applied Biology, 2024)
Indexed by Scopus